Mas?lah?ah Sebagai Metode Penggalian Hukum Islam - Syaiful Hidayat (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2013)
The primary source of Islamic law is the study of the Qur'an and hadith. From two main sources are able to produce products of Islamic legal thought resulting from the process of ijtihad. Variety of laws have dihasilakan of the ijtihad process. There qiyâs, ijmâ’, istih?sân dan mas?lah?ah. One of the discussions and debates that have been going so long is a discussion about mas?lah?ah. One group found mas?lah?ah is a controversial method used as a backrest when determining Islamic law, because mas?lah?ah is a method resulting from the intervention of human rationality in Islamic rules'. While another group found, with mas?lah?ah will be able to unravel the threads of the social problems the rest of his juridical primary sources not found in either the Qur'an or hadîth.